Ischemia/reperfusion-induced upregulation of TIGAR in brain is mediated by SP1 and modulated by ROS and hormones involved in glucose metabolism. (January 2015) - Sun, Meiling; Li, Mei; Huang, Qiao; Han, Feng; Gu, Jin-hua; Xie, Jiaming; Han, Rong; Qin, Zheng-Hong; Zhou, Zhipeng
Highlights: Glucose has no effect on TIGAR expression. Adrenaline, glucagon, and hydrocortisone increase TIGAR expression. Hormones and H2 O2 increased TIGAR expression in brain. SP1 is involved in ischemia/reperfusion-induced TIGAR upregulation. Abstract: We previously found that TIGAR (TP53-induced glycolysis and apoptosis regulator) was upregulated in response to ischemia/reperfusion insult in a TP53-independent manner. The present study sought to investigate the regulatory mechanisms of TIGAR upregulation in animal and cellular models of stroke. The animal and cellular models of ischemia/reperfusion were produced by transient middle cerebral artery occlusion and reperfusion (tMCAO/R) and oxygen–glucose deprivation/reoxygenation (OGD/R), respectively. The expression of TIGAR protein in cortical tissues and hippocampal neuronal cell line HT22 cells or primary neurons was determined. Glucose, hormones and hydrogen peroxide (H2 O2 ) were administered to mice via injection into the tail vein or lateral ventricle or directly added into cell culture medium. In mice subjected to tMCAO/R, the blood glucose level rapidly increased, peaking at 0.5 h and then declined. TIGAR protein was also significantly increased and then declined with a delayed time-course. The increase in TIGAR protein was blunted when blood glucose levels were controlled with insulin. However, administering glucose solution to mice or adding glucose to cell culture medium had no effect on TIGAR protein levels. In contrast adrenaline, hydrocortisone, glucagon and H2 O2 significantly increased TIGAR protein expression, whereas insulin inhibited TIGAR expression. The transcription factor SP1 was induced by ischemia/reperfusion ahead of TIGAR upregulation. Inhibiting SP1 with mithramycin A or silencing SP1 with siRNA blocked the ischemia-induced TIGAR upregulation. These results suggest that ROS and hormones regulating blood glucose metabolism play a role in ischemia/reperfusion-induced TIGAR upregulation.